Experimental Investigation of Electric Parameters of Alloy Diodes - Marcinkevičius, A.; Šalucha, D.; Jasonis, V. (Elektronika ir Elektrotechnika, 2005)
Dependences of forward and backward voltages of diodes on silicon disc resistivity, on silicon disc’s thickness, dependences backward characteristics on duration of etching in HF acid and forward and backward dependences on alloying temperature profile was investigated. The obtained experimental investigation results confirm that decreasing of resistivity values increases forward characteristics. Experimental investigation results confirm that if we need to get lower values of forward characteristics, we must reduce silicon disc’s thickness, limiting resistivity. The influence of surface etching on backward characteristics was investigated. Determined that extending duration of etching in HF acid, eliminates excess of Al – Si layer and brings close to pn junction, which is covering with polymeric rubber. Dependences of electrical characteristics on alloy profile’s third’s zone temperature was collected. It was proved, that changing of third’s zone doesn’t a big influence to forward characteristics. Determined that innermost depth of pn junction available when it is the lowest temperature of third zone. The results of investigation was used for control of parameters of technological processes. Ill. 14, bibl. 7 (in Lithuanian; summaries in Lithuanian, English and Russian).